Spin disorder control of topological spin texture - Hongrui Zhang; Yu-Tsun Shao; Xiang Chen; Binhua Zhang; Tianye Wang; Fanhao Meng; Kun Xu; Peter Meisenheimer; Xianzhe Chen; Xiaoxi Huang; Piush Behera; Sajid Husain; et al. (Nature Communications, 2024)
Abstract Stabilization of topological spin textures in layered magnets has the potential to drive the development of advanced low-dimensional spintronics devices. However, achieving reliable and flexible manipulation of the topological spin textures beyond skyrmion in a two-dimensional magnet system remains challenging. Here, we demonstrate the introduction of magnetic iron atoms between the van der Waals gap of a layered magnet, Fe3GaTe2, to modify local anisotropic magnetic interactions. Consequently, we present direct observations of the order-disorder skyrmion lattices transition. In addition, non-trivial topological solitons, such as skyrmioniums and skyrmion bags, are realized at room temperature. Our work highlights the influence of random spin control of non-trivial topological spin textures.